Rectal atresia with a formed anus in a five-month-old male infant (case report) (Herald of the National Children's Medical Center, 2025)
Rectal atresia with a formed anus is a rare disease, the frequency of which is 0.3–1.2% among anorectal malformations. The anomaly is characterized by the absence of a connection between the normally developed anal canal and the distal part of the rectum. In most cases, there is no fistulous communication with the urethra or vagina, while the pelvic structures, including the internal and external sphincters, are well formed. One of the variants of this anomaly is also considered to be stenosis in the distal colon. These forms belong to rare regional variants of anorectal malformations [1,3]. Various treatment approaches have been published, but the ideal tactic remains to restore intestinal continuity while maximizing the preservation of the anatomical structures of the perineum.
Keywords: rectal atresia; formed anus; anorectal malformations; sigmoid colostomy; PSARP; pediatric surgery